Contribution of Fuel Wood Income from Natural Forests to Household Economy in Delanta District, Northeastern Ethiopia - Sintayehu Eshetu; Yemiru Tesfaye (International Journal of Forestry Research)
For Ethiopia’s rural homes, particularly those in the Delanta district, fuelwood is the primary energy source. This suggests that the impact of fuel wood from the forest to family energy use or income is significant. The goal of the current study was to estimate how much annual fuel wood harvested from forests contributes to household consumption and monetary income. 96% of the forest’s income comes from fuelwood. In the study area, it contributes 2,013,539 Birr, or 33%, of all family income. 703,014 ETB, or 23.8% of the total subsistence income, and 1,310,525 ETB, or 40.65% of the total cash income of the tested households, are both covered by fuelwood from the forest. Both socioeconomic and physical characteristics close to the users influenced how dependent a household was on fuelwood income from the forest. The data obtained from randomly selected households by survey method have been subjected to multiple regression analysis and obtained that households’ reliance on fuelwood income from the forest was significantly influenced by factors such as age, educational level, number of trees owned, distance to forest, distance to market, and nonforest income, all of which had a negative and significant impact. The only significant factor that significantly and positively influences reliance on fuelwood income from the forest is the number of family members. Therefore, preserving a natural forest through the use of alternative energy sources, such as electricity, or encouraging a plantation on one’s own property is a potential discipline for mandating climate change prevention.